PERBANDINGAN PEROLEHAN BATUBARA CAIR (YIELD) ANTARA BATUBARA RANK RENDAH DENGAN RANK MENENGAH PADA BATUBARA FORMASI WARUKIN, KAB. TABALONG, KALIMANTAN SELATAN - Nursanto, Edy; Idrus, Arifudin; Amijaya, Hendra; Pramumijoyo, Subagyo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Research focusing on the quality of coal in Warukin Formation has been conducted in coal outcrops located on Tabalong area, particularly in 3 coal seams, namely, Wara 120 which is low rank coal, then Tutupan 210 and Paringin 712 which consist of medium rank coal. The average coal quality for seam Wara 120 consist of inherent moisture (IM): 26.65%, whereas for ash and volatile matter (VM) is (ash:5.08%; VM=43.98%). Beside that for fixed carbon (FC) is 24.29%. Meanwhile for seam Tutupan 210 consist of inherent moisture (IM) is 18.42%, ash:1.81%, FC: 33,88% and Paringin 712 consist of inherent moisture (IM) is 16.84%, ash:1.36% VM: 23.02% and FC: 35.76%. Coal liquefaction is conducted of coal -200 mesh(1g) in an autoclave on low pressure and temperature. Pressure during the process is 14 psi and temperature is 120oC. Research was designed by using time variable, respectively, 30 60, 90 minutes. Conversion result gained will be associated with the length of yield process. The aim on the coal liquefaction process is coal liquid. The process is conducted on the time variables of 30, 60 and 90 minutes with following results: seam Wara 120 is 35,76% (30 minute),40.68% (60 minute), 31.15% (90 minute). Then Tutupan 210 and Paringin seam are 7,64% (30 minute): 14,51% (60 minute), 4,53% (90 minute) and 3,21% (30 minute): 9.57% (60 minute), 1,71% (90 minute). Due to characteristic of coal that Wara 120 seam have H/C ratio higher than Tutupan 210 and Paringin 712, so the average result of yield shows that coals in Wara has higher yield conversion than coals in seam Tutupan and Paringin.